The impact of planning and regulatory delays for major energy infrastructure - Genaro Longoria; Muireann Lynch; Niall Farrell; John A. Curtis (The Economic and Social Research Institute (ESRI), 2022)
Effective planning and regulatory processes ensure orderly energy systems. Often, decisions are not made within mandated time frames or discrete consent processes are infrequent. Where multiple consent processes exist in sequence, a given delay may be compounded. These factors can negatively affect system costs and, ultimately, consumer welfare. This paper uses an Irish case study to quantify these effects utilising a power system model, which is a generation and transmission expansion modelling tool designed to determine optimal investments in generation and transmission infrastructures. We show that delays have meaningful impacts on electricity prices, system emissions, infrastructure investment and system operating costs. While impacts converge once all planning has been completed, deviations occur in the intervening period. Absent a delay, our case study shows that wholesale electricity prices are up to c.10% lower for a given year, while CO2 emissions are up to 3.4% lower. Efficient regulation is therefore important to maximise consumer welfare and minimise cumulative emissions. There is a clear case for undertaking an overarching review of the entire regulatory process, particularly the interface between processes.
Keywords: 330; Erneuerbare Energie; Energieinfrastruktur; Stromnetz; Infrastrukturpolitik; Regulierung; Irland